2022
DOI: 10.1134/s1064229322040068
|View full text |Cite
|
Sign up to set email alerts
|

Early Stages of the Evolution of Chernozems under Forest Vegetation (Belgorod Oblast)

Abstract: We studied automorphic forest-steppe Luvic and Haplic Chernozems (Siltic/Clayic, Pachic) of the southern part of the Central Russian Upland (Belgorod region), which were covered with broadleaved forest vegetation at different times (from 25 to 75 years ago). The studies were carried out on an overgrowing fallow and the adjacent maple-ash shelterbelt and on an area of growth of a natural oak forest towards the virgin meadow steppe. The line of effervescence in the soil profiles descended by 12-25 cm during 60-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The secretion of soil microorganisms also increased SOC and available nutrient contents, which is consistent with the findings of Chen and Yang et al [15,31]. Previous studies have also suggested that tillage practices improve soil nutrient supply capacity in Chernozem [1,2]. Soil organic matter decomposition was facilitated by the favorable conditions for microbial activity and biochemical reactions, which may have led to the accumulation of SOC and soil nutrients in the 0-15 cm layer under T15+M [18].…”
Section: Relationships Between Soil Properties and Maize Yield Under ...supporting
confidence: 88%
See 1 more Smart Citation
“…The secretion of soil microorganisms also increased SOC and available nutrient contents, which is consistent with the findings of Chen and Yang et al [15,31]. Previous studies have also suggested that tillage practices improve soil nutrient supply capacity in Chernozem [1,2]. Soil organic matter decomposition was facilitated by the favorable conditions for microbial activity and biochemical reactions, which may have led to the accumulation of SOC and soil nutrients in the 0-15 cm layer under T15+M [18].…”
Section: Relationships Between Soil Properties and Maize Yield Under ...supporting
confidence: 88%
“…In agroecosystems, organic fertilizer is an essential organic carbon source, and inversion tillage has great potential to sequester carbon in arable soil. Effective tillage and fertilization measures can improve soil properties and increase crop yields [1,2]. Inversion tillage can break the plow pan, deepen the cultivated horizon, improve soil pore characteristics, and enhance soil infiltration and moisture retention capacity [3][4][5].…”
Section: Introductionmentioning
confidence: 99%